Identification of Four Novel Variants and Determination of Genotype–Phenotype Correlations for ABCA4 Variants Associated With Inherited Retinal Degenerations - Zhu, Qing; Rui, Xue; Li, Ya; You, Ya; Sheng, Xun-Lun; Lei, Bo (Frontiers in Cell and Developmental Biology, 2021)
Purpose: To describe the genetic and clinical features of 17 patients with ABCA4-related inherited retinal degenerations (IRDs) and define the phenotype-genotype correlations. Methods: In this multicenter retrospective study, 17 patients from 16 families were enrolled, and ABCA4 gene variants were detected using targeted next-generation sequencing using a custom designed panel for IRDs. Sanger sequencing and co-segregation analysis of the suspected pathogenic variants were performed in the family members. The pathogenicities of variants were evaluated according to American College of Medical Genetics and Genomics guidelines (ACMG). Protein structure modifications mediated by the variants were studied using bioinformatic analyses. Results: The probands were diagnosed with Stargardt disease 1 (7), cone-rod dystrophy type 3 (8), cone dystrophy (1), and retinitis pigmentosa 19 (1). Onset of symptoms occurred between 5 and 27 years of age (median age=12.4 years). A total of 30 unique ABCA4 suspicious pathogenic variations were observed, including 18 missense mutations, seven frameshift mutations, two nonsense mutations, one canonical splice site mutation, one small in-frame deletion, and one insertion. Four novel ABCA4 variants were identified. Two novel frameshift variants, c.1290dupC (p.W431fs) and c.2967dupT (G990fs), were determined to be pathogenic. A novel missense variant c.G5761T (p.V1921L) was likely pathogenic, and another novel missense c.C170G (p.P57R) variant was of undetermined significance. All ABCA4 variants tested in this study inordinately changed the physico-chemical parameters and structure of protein based on in silico analysis. Conclusion: ABCA4-related IRD is genetically and clinically highly heterogeneous. Four novel ABCA4 variants were identified. This study will expand the spectrum of disease-causing variants in ABCA4, which will further facilitate genetic counseling.